Human Rights And Siyasah Syar’iyyah: Review of The Medina Charter And The Cairo Declaration - Khamami Zada (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Human rights are still a serious debate among Muslims, even though the Medina Charter and the Cairo Declaration have established the universality of human rights. This study describes the contents of human rights in the Medina Charter and the Cairo Declaration and analyzes them from the perspective of siyasah syar'iyyah. Using a qualitative approach derived from secondary data, this study finds that the Medina Charter and the Cairo Declaration are relevant to the principle of human rights. The determination of human rights in the Medina Charter and the Cairo Declaration corresponds to the two categories of siyasah syar'iyyah, namely siyasah tasyri'iyyah and siyasah dawliyyah. In siyasah tasyri'iyyah, human rights values are formed by state bodies that provide legal certainty. In siyasah dawliyyah, human rights values are determined by Muslim countries as a response to international human rights initiated by Western countries. Keywords: human rights, Medina Charter, Cairo Declaration, siyasah syar’iyyah Abstrak Hak Asasi Manusia (HAM) hingga kini masih menjadi perdebatan serius di kalangan umat Islam, meskipun Piagam Madinah dan Deklarasi Kairo telah menetapkan universalitas HAM. Studi ini mendeskripsikan muatan HAM dalam Piagam Madinah dan Deklarasi Kairo dan menganalisisnya dengan perspektif siyasah syar’iyyah. Dengan pendekatan kualitatif yang bersumber dari data-data sekunder, studi ini menemukan bahwa Piagam Madinah dan Deklarasi Kairo relevan dengan prinsip HAM. Penetapan HAM dalam Piagam Madinah dan Deklarasi Kairo ini sejaan dengan kategori dua siyasah syar’iyyah, yaitu siyasah tasyri’iyyah dan siyasah dawliyyah. Secara siyasah tasyri’iyyah, nilai-nilai HAM dibentuk oleh badan negara yang memberikan kepastian hukum. Secara siyasah dawliyyah, nilai-nilai HAM ditetapkan oleh negara-negara Muslim sebagai respon atas HAM internasional yang diinisiasi negara-negara Barat. Kata Kunci: Hak asasi manusia, Piagam Madinah, Deklarasi Kairo, siyasah syar’iyyah